2010
DOI: 10.2174/1874340401004010013
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity of Ultraviolet (UV) Radiation: Evaluation of UV-Blocking Efficiency of Intraocular Lens (IOL) Materials Using Retinal Cell Culture and in vitro Bioassays~!2009-06-08~!2010-02-10~!2010-03-26~!

Abstract: This work involves the evaluation of UV blocking efficiency of commercially available intraocular lens (IOL) materials using a retinal cell culture and a biological in vitro model that was developed in a previous study, as an effort to examine the sensitivity of this in vitro approach for evaluating toxicity of UV radiation on the retinal pigment epithelial cells. The human retinal pigment epithelial (RPE) cell line, ARPE-19, was cultured, and cells were irradiated with broadband UVB radiations at energy level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…As discovered, UVB exposure does induce a dose-dependent decrease in phagocytotic activity in RPE cells. The same decrease in phagocytotic activity was also reported by Youn et al [ 45 ] after the application of 0.2 and 0.4 J/cm 2 UVB on ARPE-19, while DrRPE cells displayed suppressed phagocytotic activity after exposing the cells to 4.2 J/cm 2 UVB [ 33 ]. This is cause for concern as the renewal of the photoreceptor outer segments (POS) is key in maintaining vision.…”
Section: Uvb Induced Dysregulation On In Vitro supporting
confidence: 78%
See 2 more Smart Citations
“…As discovered, UVB exposure does induce a dose-dependent decrease in phagocytotic activity in RPE cells. The same decrease in phagocytotic activity was also reported by Youn et al [ 45 ] after the application of 0.2 and 0.4 J/cm 2 UVB on ARPE-19, while DrRPE cells displayed suppressed phagocytotic activity after exposing the cells to 4.2 J/cm 2 UVB [ 33 ]. This is cause for concern as the renewal of the photoreceptor outer segments (POS) is key in maintaining vision.…”
Section: Uvb Induced Dysregulation On In Vitro supporting
confidence: 78%
“…However, immediately after irradiation, the morphology of mitochondria was shortened and no longer moving with very few branched mitochondria remaining within the cells [114]. Comparable conditions were also reported by Youn et al [45], whereby fewer, shorter, fragmented, and merged mitochondria were seen after UVB exposure.…”
Section: Uvb Activates Intrinsicsupporting
confidence: 77%
See 1 more Smart Citation
“…8 However, to our knowledge human studies showing UV-induced ocular surface oxidative stress are not found in the literature. This void in our knowledge base and the scientific literature is a barrier to progress in the field for development of viable effective methods to reduce or eliminate ocular disease induced by UV exposure.…”
mentioning
confidence: 87%
“…Nowadays, the increased ultraviolet radiation has been becoming one of the global environmental problems in recent years is very harmful to human health [1][2][3] , which leads to sunburn cells, premature skin aging, tanning, DNA and an increased risk for skin cancers [4][5][6][7][8][9][10][11][12] . Sensitive skin in the sun after continuous UV-B and UV-A radiation can damage DNA to decreased immunity and even cause skin cancer.…”
Section: Introductionmentioning
confidence: 99%